MINAT SERTIFIKASI PROFESI AKUNTAN OLEH CALON AKUNTAN - Bambang Bambang; Siti Atikah (Jurnal Riset Akuntansi, 2018)
This research is about the awareness of accounting students to carry out accounting profession certification, as a Public Accountant (CPA), Management Accountant (CIMA), Internal Auditor (CIA) and Fraud Auditor (CFE). Research results show that professional certification as a Public Accountant (CPA), is still considered superior compared to 3 other professional certifications that are not even fully known. However, even the profession of as Public Accountant is still quite superior, students still prefer to pursue careers as civil servants or general accountants in companies as financial report compilers. Students percieved that by having a profession certification there will be better and easier job opportunities to get a promotion, a high salary, and a reputation. This research has significant implications for professional organizations to be more active in the socialization of the existence of each profession. Whereas for universities and accounting programs can be a reference to balance professional recognition in the curriculum for all accounting profession.